Perbedaan Penggunaan Daun Sirih terhadap Waktu Penyembuhan Luka Perineum - Siti Lely Candra Kurniawati; Maria Ulfa (Journal of Ners and Midwifery, 2015)
Betel leaves are plants that contain essential oils that consist of bethephenol, chavicol, cavibetol, estrogen, eugenol, and karvarool wherein biochemical substances in a betel leaf (Piperbetle Linn) has the power to kill bacteria and fungi, also an antioxidant which accelerate the wound healing process. Method: The study used True Experimental Design, Post Test Only Control Group Design. The population in this study was 18 puerperal women in the village Ringginanyar. The sampling technique used purposive sampling. The number of sample was 16 puerperal women in the village Ringginanyar. This research was conducted on 20 July 2015â€“02 August 2015. The statistical test used Mann Whitney U - Test . Result:The results showed that the perineal wound healing time women without treatment with betel leaf the majority (62.5%) experiencing perineal wound healing on day 8, while women do treatment using betel leaves the vast majority (62.5%) experiencing perineal wound healing on day 5. Based on the findings of Mann Whitney U test -Test seen that sig value (0.00 ) < ï¡ ( 0.05 ) it could be concluded that there were differences in perineal wound healing time between groups used betel leaf and groups that did not use betel leaves .